Empowering Pharmacists: Strategies for Addressing the Opioid Crisis through a Public Health Lens - Tamera D. Hughes; Juliet Nowak; Elizabeth Sottung; Amira Mustafa; Geetha Lingechetty (MDPI AG, 2024)
Background: The opioid crisis in the US is a severe public health issue, prompting pharmacists to adopt various strategies for prevention, harm reduction, treatment, and recovery. Despite progress, barriers persist. Results: This commentary examines five determinants of public health in relation to pharmacist-led interventions for the opioid crisis: individual behavior, social factors, policymaking, health service accessibility, and biological/genetic considerations. Pharmacists can influence individual behavior through education and support, address social determinants like stigma, advocate for policy changes, ensure health service accessibility, and personalize opioid prescriptions based on biological factors. Conclusion: Pharmacists play a crucial role in addressing the opioid crisis by navigating these determinants. Pharmacists' engagement is essential for reducing opioid-related harms and improving public health outcomes through advocacy, service provision, and education.